LA IMPORTANCIA DEL USO SISTEMATICO DE ESCALAS DE DEPRESION EN CESACION TABAQUICA - Julieta Juana Cassone; Sandra Noemi Braun; Roberto Fayanas (European Scientific Journal, ESJ, 2015)
Depression is currently the 4th cause of global impairment, with a 15%-20% prevalence rate. The World Health Organization predicts that depression would become the first global morbility cause by 2030. Tobacco addiction prevalence of the general population is 25%, while in patients with psychiatric diseases, it ranges between 60% and 90%, depending on the disease. Also, the incidence of depressive disorders on smokers doubles the incidence on non smokers. Both pathologies are closely related, and demand tobacco cessation professionals to check for depression. Straightening of this variable makes tobacco cessation much easier, as well as accomplishing other life goals which is previously out of reach. Routine use of evaluation scales can save time, enhance treatment decisions, and reduce clinical mistakes. PHQ-2 scale allows the detection of depressive mood by means of two questions, with a sensibility of 83% and a specificity of 92%. The scale was validated on 6000 patients. This paper thus proposes the routine use of the PHQ-2 scale on tobacco cessation patients.